ANALISA PENGARUH VARIASI TEMPERATURE DAN WAKTU AGING PERLAKUAN PANAS T6 TERHADAP FER(factor efektivitas rem) DARI BAHAN KOMPOSIT ALUMINIUM ABU DASAR BATU BARA - Seputra, Harjo; Agustia Wardani, Ripan (Program Studi Teknik Mesin, Universitas 17 Agustus 1945 Surabaya, 2016)
Composite is a kind of material which has srtuktur of two more phases authors, namely: filler(filler) and matrix (Sciti, D., et.all., 2011). The combination of material Al Alloy with bottom ashcoal ash, classified in types of composite materials, namely Metal Matrix Composite (MMC). In the MMC material engineering process, can be used as the matrix aluminum metal alloyas filler (filler). Metal Al as a monolithic, when in the review of mechanical properties, such as hardness(hardness) is very low. Therefore, the metal Al as a monolithic material has many weaknesses, notably: mechanical strength, stiffness and coefficient expansion. The advantages of metal Al, among others have:light weight, corrosion resistant, and easy in the form of(Casting). T6 heat treatment processis to conduct dissolution with treathment solution that specimenis heated at a temperature of 5400C and held for 6 hours and then in quenching is rapidly cooled specimen with water up to media at room temperature. Furthermore, the aging processis then performed again with variations in the specimen is heated and the temperature has been determined that the first nine specimens with a temperature of 1600C detained 3 hours, 5 hours, 7 hours, then another specimen 9 1800C detained 3 hours, 5 hours, 7 hours, and 9 specimens 2000C arrested last 3 hours, 5 hours, 7 hours and then cooled slowly to room temperature. From the results of research to get the final hardness testing and FER. Effect of aging temperature on the value of FER and violence are varied temperature range, the higher the aging temperature FER value increases, so does the value of violence. The highest value of 0.631742 FER is achieved at a temperature of 2000C aging and the highest hardness valueis achieved at a temperature of 1800C with a score of 70HRF. Effect of aging time variation of the value of FER and violence is at varied time spans, the longer aging FER value increases, so does the value of violence. The highest value of 0.631742 FER is achievedÂ at a time of 7 hours and achieved the highest hardness value of 3 hours with a score of 70HRF.Keywords: Composites, T6 heat treatment process, mechanical properties, FER.